Asylum Seekers in the European Union : Building Evidence to Inform Policy Making - World Bank Group (World Bank, Washington, DC, 2018)
In 2015 and 2016, migrant flows into the European Union (EU) surged, with Greece and Italy the main entry points. Many of the migrants applied for international protection in Europe, becoming asylum seekers. This spike in EU asylum seekers, as well as the increasing numbers of those granted refugee status, brought a need for information on who they are their sociodemographic characteristics; their education and work experience; their experience on the journey to Italy and Greece; and what it cost them not only financially but also physically and emotionally to get there. This study took a rigorous approach to ensure that it produced hard data to support policy decisions, decisions made not only in receiving countries but also in countries of origin and transit. This report then, contributes to knowledge of aspects of migration and forced displacement, but much more has yet to be learned.